Element mobility from the copper smelting slag recycling waste into forest soils of the taiga in Middle Urals - Zolotova, Ekaterina S.; Ivanova, Natalya S.; Ryabinin, Viktor F.; Ayan, Sezgin; Kotelnikova, Alla L. (Springer Science and Business Media LLC, 2020)
The article presents the results of assessing the element mobility (chemical elements and compounds) from the copper smelting slag recycling waste into brown forest soils (Haplic Cambisols) of the southern taiga district in Middle Urals, Russia. The copper smelting slag recycling waste was obtained by crushing the cast slag of the Sredneuralskiy Smelter ("technical sand") followed by flotation extraction of copper concentrate. The investigations were carried out in two forest types, distinguished according to the principles of the genetic forest typology, cowberry shrub pine forest and berry pine forest with linden, and the corresponding clear-cuttings. We conducted the experiment in the autumn before the snow cover was established in two variants: (i) we evenly scattered 1 kg of waste on meter sample plots; (ii) we weighed the "technical sand" by 100 g, packed it in non-woven material and buried it in the soil to a depth of 7-10 cm. Two years later, we dug up the bags with waste and weighed them. The analyses were performed by inductively coupled plasma mass spectrometry using Elan-9000 ICP mass spectrometer. As a result of the research, it was found that waste loses 11% mass over 2 years of being in forest soils. The content of Zn, As, Cd, and Se changes most strongly. The difference in the degree of element migration from the "technical sand" to the brown forest soils of the two forest types and clear-cuttings was revealed. The study of the effect of technogenic waste on the dominant and diagnostic species of grassy vegetation in the selected forest ecosystems of the Middle Urals was carried out. There was no negative effect on the qualitative composition of the grassy layer of two forest types and their clear-cuttings after 1 year after a single surface application of mineral waste at a concentration of 1 kg/m2.
Keywords: Soil; Taiga; Forests; Copper; Ecosystem; Russia; 13. Climate action; 15. Life on land; 12. Responsible consumption